Shame as a Mediator Between Body Dissatisfaction and Disordered Eating Attitudes - Moreau, Samuel; Bennett, Laura; Matthews, Brian (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: This study aimed to investigate the mediating role of shame in the relationship between body dissatisfaction and disordered eating attitudes among Canadian adolescents and young adults. Methods and Materials: A descriptive correlational design was employed with a sample of 400 participants aged 16 to 30 years, selected based on the Morgan and Krejcie sample size table. Participants were recruited from across Canada and completed standardized questionnaires, including the Body Shape Questionnaire (BSQ-34), the Experience of Shame Scale (ESS), and the Eating Attitudes Test-26 (EAT-26). Data were analyzed using SPSS-27 for descriptive statistics and Pearson correlation coefficients, and AMOS-21 was used to perform structural equation modeling (SEM) to examine both direct and indirect pathways between the study variables. Findings: Descriptive statistics showed high mean scores for body dissatisfaction (M = 92.36, SD = 18.47), shame (M = 71.84, SD = 15.22), and disordered eating attitudes (M = 24.57, SD = 9.13). Pearson correlation results indicated significant positive relationships between body dissatisfaction and shame (r = .58, p < .001), body dissatisfaction and disordered eating attitudes (r = .63, p < .001), and shame and disordered eating attitudes (r = .56, p < .001). SEM results revealed a good model fit (χ²/df = 2.11, CFI = 0.97, RMSEA = 0.052). Shame significantly mediated the relationship between body dissatisfaction and disordered eating attitudes (indirect effect: b = 0.13, β = 0.24, p < .001), while the direct path remained significant (b = 0.38, β = 0.46, p < .001), indicating partial mediation. Conclusion: The findings highlight shame as a significant emotional mechanism that partially explains the relationship between body dissatisfaction and disordered eating attitudes. Addressing shame in prevention and intervention efforts may be crucial in reducing disordered eating among adolescents and young adults experiencing body image concerns.